J.-A. Dickmann & A. Heinemann (eds.), Vom Trinken und Bechern Das antike Gelage im Umbruch - Drougou, Stella (Journal of Hellenistic Pottery and Material Culture, 2017)
An exhibition of more than seventy objects was presented at the Antikensammlung of the University of Freiburg in spring 2015. Entitled ›Vom Trinken und Bechern. Das antike Gelage im Umbruch‹ it lasted from 26 April to 28 June. It consisted of mostly ancient Greek clay vessels of Classical and Hellenistic times, which were associated with the ancient symposium on account of either their use or their iconography. A catalogue complemented the exhibition focusing on the central theme, i.e. the symposium, which has often preoccupied archaeological research – and continues to do so – posing several individual questions on the related objects, drinking vessels and tableware or on the social and anthropological aspects of the institution itself. We should remember the 1990 exhibition in Munich on a related theme and the accompanying publication on the ›Kultur des Trinkens, Kunst der Schale‹ (ed. K. Vierneisel – B. Kaeser), though with a diﬀerent emphasis than the one in Freiburg. At the same time, new studies and research programs on the subject of wine, the architectural space of the symposium and its relation to funerary or other religious activities are constantly coming up in scholarly literature. This conﬁrms the central role, in every sense, held by the ancient symposium not only in the archaeological or historical research but also in the education of younger archaeologists on topics in antiquity. We believe that the latter has been one of the intentions of publishing the catalogue of the Freiburg exhibition. Yet, several difficult historical and methodological issues are addressed as well in the treatment of the relevant archaeological material, first and foremost the pottery.